PENERAPAN PEMBELAJARAN ILMU TAJWID DAN TILAWAH AL-QUR’AN DALAM MENINGKATKAN KUALITAS BACAAN AL-QUR’AN SISWA DI MTS ISLAMIYAH MEDAN - Ahmad Syarif Munawar; Selamat Pohan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to explore the implementation of learning the science of tajwid and Al-Qur'an recitations at MTS Islamiyah Medan for class VII students. Using a qualitative approach, this research involves direct observation, interviews with education stakeholders, and document analysis. The results show that with careful planning, effective teaching strategies, and comprehensive evaluation, the learning succeeded in improving the quality of students' reading of the Koran. Students' enthusiasm and active involvement in learning reflects the success of this learning approach. The comprehensive evaluation also showed an increase in students' attitudes, knowledge and skills in reading the Koran. In conclusion, the implementation of learning the science of tajwid and Al-Qur'an recitations at MTS Islamiyah Medan has had a significant impact in improving the quality of Al-Qur'an reading for class VII students.